Factors influencing extent of surgery for Substernal Thyroid Goiters: Hemithyroidectomy versus total Thyroidectomy - Anne C Kane; Brian J Johnson; Michael DiLeo; Jeffrey Hotaling; Anna Pou; Daniel W Nuss; Rohan Walvekar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Background: When compared to removal of cervical goiters, patients undergoing removal of substernal goiter have been found to have higher rates of complications, including recurrent laryngeal nerve injury, bleeding, and hypoparathyroidism. Previous literature has discussed hemithyroidectomy versus total thyroidectomy for cervical goiters showing that the less invasive procedure was a reasonable option with decreased morbidity overall.  Methods: A retrospective chart review was performed at 2 tertiary academic medical centers. The search was performed using the CPT codes for substernal removal of thyroid 60270 and 60271.  Results: 38 patients were identified between the years 2011-2017. Patients who underwent hemithyroidectomy in this study, had a trend toward older age, higher rate of medical co-morbidities and small size of non-dominant thyroid lobe. No patients who underwent hemithyroidectomy at this institution during this study period required completion thyroidectomy.  Conclusion: Hemithyroidectomy is an acceptable treatment option for substernal goiters in appropriate cases.